Dynamic damage analysis of carbon fiber reinforced polymer composite pressure vessels (Fracture and Structural Integrity, 2025)
This study investigates spall damage and failure in Carbon Fiber-Reinforced Polymer (CFRP) pressure vessels under explosive internal loading using stimulated electric discharge. Analytical modeling, validation with published experimental data, and explicit numerical simulations were employed. A Coupled Eulerian–Lagrangian (CEL) framework in Abaqus/Explicit captured the dynamic-impact shock propagation, using continuum shell (SC8R) elements for the vessel, solid (C3D8R) for the PMMA insert, and Eulerian (EC3D8R) for copper-wire vapor. Intralaminar failure was modeled using the Hashin criterion, while interlaminar damage was captured using the energy-release-rate-tuned Virtual Crack Closure Technique (VCCT). Results demonstrated high-accuracy agreement with experiments in terms of free surface velocity and failure stresses, with minor discrepancies attributed to wire alignment, material model limitations, and wave reverberations. These findings highlight the reliability of the integrated modeling framework and support improved design and risk-mitigation strategies for composite pressure vessels, advancing safety and cost-efficiency through refined material characterization and structural assessment.
Keywords: explicit; numerical; spall; damage; CFRP; composite vessels; explosive; dynamic; impact; Hashin; VCCT